Respuesta :
Answer:
x = - 1 and x = 5
Step-by-step explanation:
Given
(x - 3)² + 2(x - 3) - 8 = 0
Let u = x - 3, then
u² + 2u - 8 = 0 ← solve for u
(u + 4)(u - 2) = 0 ← in factored form
Equate each factor to zero and solve for u
u + 4 = 0 ⇒ u = - 4
u - 2 = 0 ⇒ u = 2
Convert back to x, that is
x - 3 = - 4 ( add 3 to both sides ) ⇒ x = - 1
x - 3 = 2 ( add 3 to both sides ) ⇒ x = 5
Answer: The correct option is
(B) x = -1 and x = 5.
Step-by-step explanation: We are given the following equation :
[tex](x-3)^2+2(x-3)-8=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
We are to find the solutions of the above equation.
Let u= (x-3).
Then, from equation (i), we have
[tex]u^2+2u-8=0\\\\\Rightarrow u^2+4u-2u-8=0\\\\\Rightarrow u(u+4)-2(u+4)=0\\\\\Rightarrow (u-2)(u+4)=0\\\\\Rightarrow u-2=0,~~~~~~~~~~~~u+4=0\\\\\Rightarrow x-3-2=0,~~~\Rightarrow x-3+4=0\\\\\Rightarrow x=5,~x=-1.[/tex]
Thus, the required solution is x = -1 and x = 5.
Option (B) is CORRECT.